2023
DOI: 10.1111/evj.13923
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and oral bioavailability of cannabidiol in horses after intravenous and oral administration with oil and micellar formulations

Abstract: BackgroundIntravenous pharmacokinetics and oral bioavailability of cannabidiol (CBD) with different formulations have not been investigated in horses and may represent a starting point for clinical studies.ObjectivesTo describe pharmacokinetics after intravenous and oral administrations with oil and micellar formulations and simulate different treatments.Study designSingle intravenous experiment and two‐way randomised oral experiments, Latin‐square design.MethodsEight healthy horses received intravenous CBD at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…Like in other equine and small animal investigations, the pharmacokinetic analysis showed a rapid increase of CBD in serum following oral administration ( 15 , 16 , 28 , 29 , 50 55 ). The values for C max were similar to those calculated in other studies ( 28 31 , 33 ). In contrast, the AUC 0–12 h values obtained here differ significantly.…”
Section: Discussionsupporting
confidence: 89%
“…Like in other equine and small animal investigations, the pharmacokinetic analysis showed a rapid increase of CBD in serum following oral administration ( 15 , 16 , 28 , 29 , 50 55 ). The values for C max were similar to those calculated in other studies ( 28 31 , 33 ). In contrast, the AUC 0–12 h values obtained here differ significantly.…”
Section: Discussionsupporting
confidence: 89%
“…Because CBD is a BCS II molecule, it is challenging to formulate a parenteral solution. A few authors have studied the intravenous kinetics of CBD by injecting Cremophor ® emulsion, suspensions containing Tween ® , or propylene–ethanol solutions in mice or humans [ 35 , 36 , 37 ]. In our study, the cyclodextrin (CD) strategy was chosen in accordance with previous work in our laboratory [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…( 8 , 66–71 ). Two studies found C max levels of 51 ng/mL CBD in serum following oral administration of 2 mg CBD/kg SID for 7 days ( 67 , 70 ), and C max levels of 55.7 ng/mL CBD in serum following a single oral dose of 10 mg CBD/kg ( 72 ). The C max levels of 38.4 ± 8.9 ng/mL in serum reported during the current study ( 63 ) are therefore in line with previous reports, and comparatively high ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may also include more detailed assessments of HRV parameters including the parasympathetic tone activity (PTA) index. Oral dosing using different formulations such as micellar formulation should also be considered ( 72 ). Clinical studies as have been performed with dogs ( 4 ) are of interest to further assess the potential use of CBD in equine medicine.…”
Section: Discussionmentioning
confidence: 99%